THE STRUGGLE BETWEEN SPIRITUALITY AND SEXUALITY IN "SONS AND LOVERS" BY D. H. LAWRENCE (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
This research paper explores the complex interplay between spirituality and sexuality in D. H. Lawrence's Sons and Lovers. Through an analysis of the novel's key characters, particularly Paul Morel, the paper examines how these two forces manifest in the protagonist's relationships and inner conflicts. Spirituality, often depicted through Paul's bond with his mother, is shown as a source of moral and emotional guidance, while his sexual desires introduce a tension that challenges his sense of self and belonging. The struggle between these two aspects of his identity becomes a central theme, reflecting broader societal conflicts of the time. This paper aims to shed light on how Lawrence uses this struggle to comment on the complexities of human desires, the nature of familial ties, and the quest for individual freedom.